ANALISIS RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, DAN CAPITAL PADA PERBANKAN YANG MELAKUKAN MERGER AKUISISI TAHUN 2008-2011 - Trijayadi, Anton (Arthavidya Jurnal Ilmiah Ekonomi, 2016)
ABSTRACT. Banking is one sector that is influential in boostingthe economy, especially in Indonesia. To maintain stability, the bankmust have strategy in order to survive or to grow larger, such as amerger or acquisition. This study aimed to analyze the objective RiskProfile, Good Corporate Governance, Earnings and Capital in thebanking of merger acquisition in 2008-2011. In this study, the dataobtained from the three banks of merger acquisition and analyzedusing Paired Sample T-Test. The results of this study refer that theperformance of the bank as a variable NPL, LDR, the Board ofIndependent Commissioners in three banks do not have significantdifferences. Variable Audit Committee, ROA, NIM and ROA showstwo banks do not have significant differences and one bank has asignificant difference. Variable CAR indicates one bank do not havesignificant differences, and two banks have a significant differencebetween before and after the bank merger acquisition. This study referthat the process of merger acquisition has not succeeded as expected.Keywords : Bank, Banking, Mergers, Acquisitions, RGEC, BankHealth Level, Financial Performance